2017
DOI: 10.1002/acm2.12208
|View full text |Cite
|
Sign up to set email alerts
|

Verification of junction dose between VMAT arcs of total body irradiation using a Sun Nuclear ArcCHECK phantom

Abstract: A volumetric modulated arc therapy (VMAT) approach to total body irradiation (TBI) has recently been introduced at our institution. The planning target volume (PTV) is divided into separate sub‐volumes, each being treated with 2 arcs with their own isocentre. Pre‐treatment quality assurance of beams is performed on a Sun Nuclear ArcCHECK diode array. Measurement of junction regions between VMAT arcs with separate isocentres has previously been performed with point dose ionization chamber measurements, or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…ArcCHECK allows measurement of treatment eld length ≤20 cm in a single irradiation. Our protocol is in alignment with other studies wherein several authors have reported veri cation of absolute dose and uence either section by section or in the junction of two consecutive arcs using various detectors and methods [7,11]. In addition, for each patient we also carried out in-vivo EBT3 lm dosimetry a) at eleven pre-de ned locations across the whole body and b) in the junction region of upper and lower body treatment plans to ensure delivery of homogeneous dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ArcCHECK allows measurement of treatment eld length ≤20 cm in a single irradiation. Our protocol is in alignment with other studies wherein several authors have reported veri cation of absolute dose and uence either section by section or in the junction of two consecutive arcs using various detectors and methods [7,11]. In addition, for each patient we also carried out in-vivo EBT3 lm dosimetry a) at eleven pre-de ned locations across the whole body and b) in the junction region of upper and lower body treatment plans to ensure delivery of homogeneous dose.…”
Section: Discussionmentioning
confidence: 99%
“…All the commercially available active or passive detectors for patient speci c quality assurance (PSQA) have limited longitudinal and lateral dimensions of 20-25 cm to verify highly modulated mega treatment elds from TMI/TMLI especially for HT delivery. The feasibility of different detector arrays (2D or 3D) arranged in planar, hexagonal, circular and helical have been investigated for section by section dose veri cation of TBI/TMI plans [7,10,11]. Takahashi Y and Hui K S [12] developed a simple inhouse whole body phantom to verify TMI treatment plan of up to 110 cm in HT using three ionization chambers and three radiochromic lms.…”
Section: Introductionmentioning
confidence: 99%
“…ArcCHECK allows measurement of treatment field length ≤ 20 cm in a single irradiation. Our protocol is in alignment with other studies wherein several authors have reported verification of absolute dose and fluence either section by section or in the junction of two consecutive arcs using various detectors and methods [7,11]. In addition, for each patient we also carried out in-vivo EBT3 film dosimetry (a) at eleven pre-defined locations across the whole body and (b) in the junction region of upper and lower body treatment plans to ensure delivery of homogeneous dose.…”
Section: Discussionmentioning
confidence: 99%
“…All the commercially available active or passive detectors for patient specific quality assurance (PSQA) have limited longitudinal and lateral dimensions of 20-25 cm to verify highly modulated mega treatment fields from TMI/TMLI especially for HT delivery. The feasibility of different detector arrays (2D or 3D) arranged in planar, hexagonal, circular and helical have been investigated for section by section dose verification of TBI/TMI plans [7,10,11]. Takahashi and Hui [12] developed a simple in-house whole body phantom to verify TMI treatment plan of up to 110 cm in HT using three ionization chambers and three radiochromic films.…”
Section: Introductionmentioning
confidence: 99%
“…So, Delta 4, ArcCheck and Octavius 4D for dose veri cation of VMAT are more common in daily work [23][24][25].…”
Section: D Gamma Standard and Passing Ratementioning
confidence: 99%